Clinical impact of parental consanguineous marriage in idiopathic nonobstructive azoospermia - Oktay Özman, M.D.; Mustafa Emre Bakırcıoğlu, M.D. (F&S Reports, 2020)
Objective: To determine the frequency of parental consanguineous marriages (PCMs) in men with diagnosed idiopathic nonobstructive azoospermia (INOA) and to compare clinical and pathological parameters between azoospermic men with and without PCM. Design: Retrospective. Setting: A private clinic. Patient(s): Two hundred forty-six men with INOA. Patients were divided into two groups: group 1 with PCM and group 2 without PCM. Clinical parameters, surgical sperm retrieval rates, and pathological findings were compared between the groups. Intervention(s): Surgical sperm retrieval. Main Outcome Measure(s): PCM and clinical parameters. Result(s): Among the 246 patients with INOA, 81 had PCM. Men with PCM had lower follicle-stimulating hormone (13.7 vs. 21.9 mIU/mL), higher testosterone (3.8 vs. 3.4 ng/mL), and larger testes (14.1 vs. 11.8 mL). In parallel with the clinical findings, the most common pathological pattern in men with PCM was maturation arrest. However, there was no difference in surgical sperm retrieval rate between men with (23.4%) and without (32.1%) PCM. Conclusion(s): Our data showed that PCM was present for 33% of men with INOA. The clinical parameters of men with PCM and INOA were significantly different than those without PCM, primarily demonstrating maturation arrest in testicular pathology. Further genetic research in families who have infertile male siblings may elucidate underlying rare genetic abnormalities in spermatogenesis.